2005
DOI: 10.1254/jphs.fp0040184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Crude Saponin of Korean Red Ginseng on High-Fat Diet-Induced Obesity in the Rat

Abstract: Abstract. The anti-obesity effects of crude saponin (CS) of Korean red ginseng (KRG) were investigated in the rat fed a high-fat (HF) diet. Male Sprague-Dawley (SD) rats became obese by feeding the HF diet over 5 weeks, while the control rats were fed a normal diet, and then both groups were treated with CS (200 mg / kg, i.p.) for 3 weeks. The body weight, food consumption, adipose tissues, and expression of appetite peptides such as leptin and neuropeptide Y (NPY) were investigated in rats fed normal and HF d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
123
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(134 citation statements)
references
References 51 publications
9
123
0
2
Order By: Relevance
“…These results suggest that KGE exerts the anti-obesity effect as well as a hypolipidemic effect in HFD-induced obese mice. And they are in accordance with previous reports that the supplementation of ginseng extracts and ginsenosides has anti-obesity and hypolipidemia in HFDinduced obese animals and obese type 2 diabetic animals, in spite of not showing the anti-diabetic effect in other reports (Yamamoto et al 1983;Chung et al 2001;Attele et al 2002;Yoon et al 2003;Yun et al 2004;Kim et al 2005;Karu et al 2007). We expect that difference would be caused by the differences in dietary fat content, feeding period, kind of experimental and components of ginseng extracts.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results suggest that KGE exerts the anti-obesity effect as well as a hypolipidemic effect in HFD-induced obese mice. And they are in accordance with previous reports that the supplementation of ginseng extracts and ginsenosides has anti-obesity and hypolipidemia in HFDinduced obese animals and obese type 2 diabetic animals, in spite of not showing the anti-diabetic effect in other reports (Yamamoto et al 1983;Chung et al 2001;Attele et al 2002;Yoon et al 2003;Yun et al 2004;Kim et al 2005;Karu et al 2007). We expect that difference would be caused by the differences in dietary fat content, feeding period, kind of experimental and components of ginseng extracts.…”
Section: Discussionsupporting
confidence: 93%
“…Ginseng extract and isolated ginsenosides displayed antihyperglycemic and anti-obesity activities following administration to diabetic rodents such as ob/ob and KKA y mice (Chung et al 2001;Attele et al 2002). Wild ginseng extract and crude saponins were also shown to reduce plasma lipid levels and obesity when administered to rodents fed a high-fat diet (Yoon et al 2003;Kim et al 2005;Karu et al 2007). Although the anti-obesity effects of ginseng and ginsenosides have been reported, the molecular mechanism by which ginseng reduces obesity in mice fed a high-fat diet is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, multiple studies reported that treatment with red ginseng extract or its functional constituents, saponins, led to a reduction in the mRNA levels of angiogenic factors (e.g., VEGF-A and FGF-2) and matrix metalloproteinases (MMPs) (e.g., MMP-2 and MMP-9), and the expression of hypothalamic neuropeptide Y (NPY) in vivo [2][3][4]25]. In addition, immature black raspberry contains large amounts of ellagic acid, which can regulate the protein levels of Nrf2, NF-κB and CPT1 in an HFD-induced rat model of metabolic syndrome [26], and has anti-obesity effects [27].…”
Section: Discussionmentioning
confidence: 99%
“…Several groups reported that the anti-obesity effect is attributed to ginseng saponins [2][3][4], which are classified into protopanaxadiol group (ginsenosides: Ra, Rb, Rc, Rd, Rg3, Rh2, and Rs) and protophanxatriol group (ginsenosides: Re, Rf, Rg1, Rg2, and Rh1) depending on their chemical structures. Red ginseng is known to contain large amounts of Rg2, Rg3, Rh1, and Rh2 ginsenosides that are effectively produced during the heating process.…”
Section: Introductionmentioning
confidence: 99%
“…In mouse studies, knockout of the gene encoding the androgen receptor results in obesity, whereas overexpression of the androgen receptor results in decreased adipose tissue mass (Rana et al, 2011; crine, immune, and cardiovascular systems (Gillis, 1997;Attele et al, 1999;Lu et al, 2009). In addition, ginseng has been suggested to reduce weight gain in animal models of obesity and can effectively regulate genes involved in obesity (Attele et al, 2002;Kim et al, 2005;Karu et al, 2007;Mollah et al, 2009;Lee et al, 2009Lee et al, , 2012. Ginseng also significantly inhibits visceral obesity and adipocyte hypertrophy (Lee et al, , 2014, which is closely associated with metabolic syndromes (Okuno et al, 1998;Jeong and Yoon, 2009;Lee et al, 2014).…”
Section: Introductionmentioning
confidence: 99%